Stock and Sauce Teaching Materials for European Culinary Courses: Vocational Education - Cokorda Istri Raka Marsiti; Ni Wayan Sukerti; Luh Masdarini; Made Diah Angendari (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
This research is motivated by learning less effective activities because educators must provide detailed information while teaching materials could be more supportive. In addition, the lack of teaching materials will make it difficult for students to carry out learning activities outside of learning hours. The research aimed to develop learning materials related to broth and sauce in European culinary courses. The study used a research and development design adapted to the ADDIE model (analysis, design, development, implementation, and evaluation). The subjects involved in this study were third-semester students of the Tata Boga study program selected by total sampling because the number of students was less than 100. The data collection methods used were document analysis, observation, interview, and questionnaire distribution. Then, the data were analyzed quantitatively and qualitatively. The research findings show that the learning materials developed as e-modules cover students' attitudes, cognition, and skills. The developed product is very feasible and has positive student responses.